Techno-Economic Design of Onshore Gas Pipelines with High CO₂ and H₂S Content - Pamungkas, Joko; Pramadewi , Indrianti; Hermawan, Yulius Deddy; Yuliestyan, Avido; Yusuf, Yusmardhany; Kurniawan, Aditya; Ramadhan, Muhammad Redo; Anggorowati, Heni; Perwitasari; Wulandari, Mutiara; Lazuardi, Muhammad Daffa (Testing Center for Oil and Gas LEMIGAS, 2026)
This study develops a simulation-based techno-economic framework for designing an onshore gas trunkline system to accommodate production from newly developed wells in the X and Y Fields. The system transports 35 MMSCFD of untreated natural gas containing approximately 60 mol% CO₂ and 70 ppm H₂S, where high acid gas content and declining wellhead pressure impose constraints on pressure delivery, flow velocity, material selection, and lifecycle cost. Steady-state hydraulic simulations were performed using UniSim R490 to evaluate early- and mid-life production scenarios based on pressure drop and erosional velocity ratio (EVR) in accordance with API RP 14E. Comparative analysis of candidate pipeline diameters shows that a 12-inch trunkline maintains a minimum delivery pressure of 50 psig while keeping EVR below unity, thereby satisfying hydraulic and mechanical integrity requirements without excessive recompression. The integration of an onshore booster compressor mitigates reservoir pressure decline and sustains gas transport to the central processing facility. Material selection analysis identifies duplex stainless steel and SS 316 as technically viable options for CO₂-H₂S service under controlled operating conditions. Techno-economic evaluation indicates that the selected configuration minimizes total lifecycle cost relative to alternative designs, with estimated CAPEX of USD 228.43 million and annual OPEX of USD 142.19 million. The results demonstrate that integrated hydraulic optimization, sour-service material selection, and economic assessment provide a robust and economically optimized design approach for onshore sour gas pipeline systems.